2007
DOI: 10.1159/000107085
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Dementia Associated with Argyrophilic Grain Disease

Abstract: Background/Aims: We aimed at characterizing the clinical features of dementia associated with argyrophilic grain disease (AgD). Methods: Relatives or close friends of 24 individuals with autopsy-confirmed AgD and 29 patients with autopsy-confirmed Alzheimer’s disease (AD) were administered a novel Retrospective Dementia Inventory to assess the cognitive, behavioral and affective symptoms of the deceased patients. Results: AgD patients showed less severe impairments in memory, language, attention and executive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Amnesia is its most common initial symptom (Ferrer, Santpere, & van Leeuwen, 2008), whereas other cognitive functions are relatively spared. However AGD usually appears in very old patients (in our sample only three patients were above 75); in addition, our TLD patients lack the behavioral disturbances (irritability agitation, delusions, and apathy) frequently reported in dementia associated with AGD (Steuerwald et al, 2007;Togo et al, 2005).…”
Section: Discussionmentioning
confidence: 48%
“…Amnesia is its most common initial symptom (Ferrer, Santpere, & van Leeuwen, 2008), whereas other cognitive functions are relatively spared. However AGD usually appears in very old patients (in our sample only three patients were above 75); in addition, our TLD patients lack the behavioral disturbances (irritability agitation, delusions, and apathy) frequently reported in dementia associated with AGD (Steuerwald et al, 2007;Togo et al, 2005).…”
Section: Discussionmentioning
confidence: 48%
“…The reason we included the study of AGs in our study design is that other researchers have reported an overrepresentation of AG pathology in TDP‐43[+] cases . We note that in our autopsy cohort , as in others , AGs were not associated with cognitive impairment independent of other pathologies, whereas AGs are associated with dementia in other cohorts . Thus, there may be a discrepancy between the diseases underlying AG pathology seen in various populations and/or autopsy cohorts.…”
Section: Discussionmentioning
confidence: 61%
“…9 In addition, it is difficult to differentiate between FTD or DLB and early-stage AD. 10 Previous reports have shown that the clinical features of AGD 11,12 and NFTPD 13,14 are indistinguishable from those of AD. In some cases, these diseases are characterized by gradually progressing dementia with prominent memory disturbances and considerable preservation of other cognitive functions.…”
Section: Discussionmentioning
confidence: 99%
“…Amyloid-b (Ab) protein is a major component of these senile plaques. Klunk et al reported that 11 C-labeled Pittsburgh compound B ([ 11 C]-PiB) has a high affinity for Ab, and [ 11 C]-PiB has been used as an amyloidimaging compound since their report was published. 1 11 Clabeled Pittsburgh compound B-positron emission tomography (PET) has shown amyloid deposition in patients with AD and in some patients with mild cognitive impairment (MCI).…”
Section: Introductionmentioning
confidence: 99%